Knowledge of human Papillomavirus among male college students - Jackan, Jennifer R. (My University, 2009)
Human papillomavirus (HPV) infection of the genital tract is the most common sexually-transmitted infection (STI) in the U.S. Over one-half of sexually active men and women are infected with HPV at some point in their lives. The highest rate of HPV infection is found in the young, sexually-active population. Seventy-four percent of new infections occur in individuals 15 to 24 years of age. Each year 6.2 million people become newly infected with HPV (Centers for Disease Control and Prevention [CDC), 2007a). Human papillomavirus can lead to cancers of the cervix, vagina, rectum, anus and penis. Women who have abnormal pap smears routinely are screened for HPV; however, there is no routine exam to screen men for infection. There have been numerous studies done surrounding women's knowledge of HPV, yet there have been very few studies done on the knowledge base of males regarding HPV infection, The purpose of this study was to explore the knowledge of male college students ages 18 to 24 about HPV infection. This age group is being used based on the number of new infections occurring among 15 to 24 year olds. The Health Belief Model (HBM) provided the framework for this study. TIle setting of this study was a student health center at a Midwestern university. The researcher used a convenience sample of 91 male college students. The researcher administered a modified 30-item questionnaire measuring the knowledge of HPV and other STls, sexual practices, sexual behaviors and demographic information. Data were analyzed using descriptive statistics to determine responses of male college students regarding their knowledge of HPV and other STls. Results showed 33% of participants did not know that HPV is an STI. Only 26.4% of participants knew that HPV causes genital warts, and 42.9% were uncertain how HPV is transmitted. Seventy-three percent of participants were very or somewhat concerned about contracting an STI and 26% were not at all concerned. A majority of participants (63%) responded with uncertainty regarding the symptoms of HPV, A disturbing finding was that condoms were used every time by only 50% of the participants. These findings indicate that further education regarding HPV is necessary among male college students.
A Clinical Paper Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science in Nursing - Family Nurse Practitioner -- University of Wisconsin-Oshkosh, 2008
Keywords: Health knowledge, Attitudes and practice; Papillomavirus Infections; Genital Diseases, Male college students; Sexually transmitted diseases